2009
DOI: 10.1002/rcm.4169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in 13C/12C of oil palm leaves to understand carbon use during their passage from heterotrophy to autotrophy

Abstract: The carbon isotope composition of leaf bulk organic matter was determined on the tropical tree Elaeis guineensis Jacq. (oil palm) in North Sumatra (Indonesia) to get a better understanding of the changes in carbon metabolism during the passage from heterotrophy to autotrophy of the leaves. Leaf soluble sugar (sucrose, glucose and fructose) contents, stomatal conductance and dark respiration, as well as leaf chlorophyll and nitrogen contents, were also investigated. Different growing stages were sampled from le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
(120 reference statements)
1
18
0
1
Order By: Relevance
“…Email: jaleh.ghashghaie@u-psud.fr given organ, for example, leaf lamina were shown to be 13 C-depleted compared with leaf ribs in different herbs and woody species (see [5] and references therein). Heterotrophic leaves (about to be emerged and not yet green) are 13 C-enriched compared with green autotrophic leaves as well [6,7]. It is concluded that fractionation mechanisms do likely occur after net CO 2 fixation in the leaves (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…Email: jaleh.ghashghaie@u-psud.fr given organ, for example, leaf lamina were shown to be 13 C-depleted compared with leaf ribs in different herbs and woody species (see [5] and references therein). Heterotrophic leaves (about to be emerged and not yet green) are 13 C-enriched compared with green autotrophic leaves as well [6,7]. It is concluded that fractionation mechanisms do likely occur after net CO 2 fixation in the leaves (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…A difference in carbon isotope composition is also observed between different tissues of a given organ; for example, leaf lamina were shown to be 13 C‐depleted compared with leaf ribs in different herbs and woody species (Badeck et al ., and references therein). Heterotrophic leaves (before photosynthetic onset) are 13 C‐enriched compared with green autotrophic leaves as well (Bathellier et al ., ; Lamade et al ., ). It is concluded that fractionation mechanisms do probably occur after net CO 2 fixation in the leaves, leading to the observed 13 C differences between autotrophic and heterotrophic tissues/organs.…”
Section: Post‐photosynthetic Discriminationmentioning
confidence: 97%
“…However, distinct differences in the use of recent vs. stored C for radial growth have been documented for deciduous trees, with some species incorporating negligible amounts of reserves . During summer, photosynthates are allocated mainly above ground (Mordacq et al, 1986;Olsrud and Christensen, 2004), supplying shoot elongation (Schier, 1970;Hansen and Beck, 1994), radial growth (Gordon and Larson, 1968), further foliage development (Dickson et al, 2000;Lamade et al, 2009) and flowering and fruiting (Mor and Halevy, 1979;Hoch and Keel, 2006). Possibly as a result of rapid mixing between old and new C (Keel et al, 2007) there is a carryover of stores for wood growth in most species (Kagawa et al, 2006b;Keel et al, 2006;von Felten et al, 2007;Palacio et al, 2011), which may impair the use of isotope tree-ring data as proxy for environmental processes.…”
Section: Temporal C Allocation Patternsmentioning
confidence: 99%